Vitamin D and the intracrinology of innate immunity - Hewison, Martin (2010)
An immunomodulatory role for vitamin D was first proposed more than 25 years ago, based on two salient observations. Firstly it was shown that monocytes/macrophages from patients with the granulomatous disease sarcoidosis constitutively synthesize the active form of vitamin D, 1,25-dihydroxyvitamin D (1,25(OH)(2)D) from precursor 25-hydroxyvitamin D (25OHD). Secondly, the receptor for 1,25(OH)(2)D (vitamin D receptor, VDR) is detectable in activated, proliferating lymphocytes. These observations suggested a mechanism whereby 1,25(OH)(2)D produced by monocytes could act upon adjacent T-cells or B-cells, but the impact of such a system on normal immune regulation was uncertain. Indeed, it is only in recent years that a much clearer picture of the role of vitamin D as a determinant of immune responsiveness has emerged. Two new concepts have prompted this change. Firstly studies of innate immunity have shown that intracrine induction of antimicrobial activity by vitamin D is a pivotal component of monocye/macrophage response to infection. Secondly, it is now clear that sub-optimal vitamin D status is a common feature of many populations throughout the world, with the potential to compromise monocyte/macrophage metabolism of 25OHD and subsequent actions of 1,25(OH)(2)D. The current review details these new developments with specific reference to the metabolic and signaling mechanisms associated with innate immune regulation by vitamin D and implications for human disease.